Growth of ZnS:Ag:Cu Thin Film Deposited on Glass Substrates using Thermal Evaporation Technique for Alpha-photovoltaic - Emy Mulyani; Tjipto Sujitno; Dessy Purbandari; Ferdiansjah Ferdiansjah; Sayono Sayono (Jurnal Sains Materi Indonesia, 2019)
This paper presents the research on the growth of ZnS:Ag:Cu thin film on a glass substrate as a radio-luminescent material. The SRIM/TRIM software is used to determine the optimum thickness based on an energy deposition depth of 5.485 MeV Am 241 alpha radiation source on ZnS:Ag:Cu material. To increase the adhesive strength of the coating, initially, the glass substrate is etched using a plasma glow discharged at 280°C for 15 minutes. Multiple coatings of ZnS:Ag:Cu were  etched on the glass substrate; this was carried out using a thermal evaporation technique to achieve the optimal thickness (based on SRIM/TRIM simulation). The thin film thickness was observed using a scanning electron microscope (SEM). The optical properties of the un-etched, etched glass substrate and thin-film were characterized using UV-Vis spectrometer. Based on SRIM/TRIM simulation, the optimal thickness is 22 mm which can be achieved by coating three times. From optical properties of ZnS:Ag:Cu thin film and after being analysed using Taue plot method, it is found that the energy gap of ZnS:Ag:Cu thin film is 2.48 eV. It can be concluded that the addition of Ag and Cu doped decrease the energy gap of ZnS (3.66 eV).